How Does Service Affect the Usage of Transportation in Indonesia: A Study Between Gojek, Grab, and Blue Bird Taxi - Nawangwulan, Irma M; Anantadjaya, Samuel PD; Samuel, DC Ethan; Samuel, Daniella Christy Eryn; Lahuddin, Abdul Haris (Apollo: Journal of Tourism and Business, 2024)
This paper examines the service marketing between three-most-popular private transportation in Indonesia which are Gojek, Grab and Blue Bird taxi. Not only will this paper discuss on the matter of service that performed by each company but also analyzed the positive outcomes and opinions about steps that needed to be taken immediately by each company. A comparison data will be performed to compare the service outcome from the customers which gotten from the primary data. The primary data contains of questionnaires that were distributed to the customers for each company. Needed to be taken into the account for each company that service marketing is one of the leading factors on how the brand image and performance of the company will be judged.